Predicting the Productivity of China’s Building Sector and the Elements that Affect it Using the DEA-Tobit Framework - Guang Cheng (Journal of Digital InformationManagement, 2024)
The total output value of the construction industry, a pillar industry of China, is continuously growing with the expansion of the production and operation scale of Chinese construction enterprises. The extensive high-input mode has promoted the economic growth of the construction industry. Despite the fruitful and outstanding results, production inefficiency has become especially prominent. Though developing rapidly, China’s construction industry possesses fewer ecological investments, accompanied by low environmental awareness and little importance to environmental protection, constantly failing to eliminate high energy consumption, high investments, and high emissions. In addition, the contradiction between the economic growth of the construction industry and the ecological environment remains evident. In this paper, the production efficiency of China’s construction industry was transversely and longitudinally measured using the DEA-Malmquist index method, followed by a further analysis of the factors influencing the production efficiency of China’s construction industry based on the Tobit regression model. The results show that the average production efficiency of China’s construction industry is the highest in the East, moderate in the West, and lowest in the centre. The number of construction enterprises, per capita capital, industrial structure, the proportion of state-owned capitals, and GDP are significant at 1%, 10%, 1%, 1%, and 1%, respectively. The research results can provide theoretical reference for reasonably establishing an ecological efficiency evaluation system for the construction industry to analyze the differences in environmental efficiency among different provinces and regions, further find out the key factors influencing ecological efficiency, propose the corresponding pertinent policy suggestions, and ultimately improve the ecological efficiency of China’s construction industry.

Predictive Modeling of Stock Price Trends Using Machine Learning and Deep Learning Techniques- - K. Kiruthika; E.S. Samundeeswari (Journal of digital information management, 2024)
<strong style="margin: 0px; padding: 0px; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-variant-alternates: inherit; font-variant-position: inherit; font-stretch: inherit; font-size: 15.2015px; line-height: inherit; font-family: Raleway, Arial, Tahoma; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; vertical-align: baseline; color: rgb(17, 17, 17); text-align: justify;">:Predicting stock price movements has been challenging yet crucial for investors and financial ana- lysts. Fluctuations in stock prices are valuable economic indicators, providing insights into overall economic well- being, consumer confidence, and market sentiment. In this study, we evaluate the efficacy of three different ma- chine and deep learning algorithms in anticipating stock price trends. We assess the performance of Logistic Re- gression, Random Forest Regression, and Long Short- Term Memory (LSTM) algorithms in forecasting whether a stock's price will rise or fall in the upcoming period, utilising historical stock price data as input features. Our findings demonstrate that while each algorithm exhibits varying degrees of predictive accuracy, LSTM networks stand out as they generally outperform Logistic Regression and Random Forest Regression in capturing the complex tem- poral dependencies inherent in stock price data. This suggests that LSTM networks, with their superior perfor- mance, hold significant promise as effective tools for stock price trend prediction, particularly in volatile and non-lin- ear financial markets. This could be a game-changer in stock price prediction, instilling optimism about the fu- ture of stock market analysis..

Public Key Cryptosystem and Binary Edwards Curves on the Ring - Moha ben taleb Elhamam (Journal of Digital Information Management, 2022)
Let be a finite ring of characteristic 2, where e2 = e and n is a positive integer. Let (a, d) 2 ( )2, such that a and d + a2 + a are invertible in , we study the binary Edwards curve over this ring, denoted by and we give a bijection between this curve and produces two binary Edwards curves defined on the finite field . Afterthat we study the addition law of binary Edwards curves over the ring . We end this work with cryptography applications, ElGamal twisted Edwards curve cryptosystem and Cramer-Shoup twisted Edwards curve cryptosystem.

Prediction of Reviews Rating: A Survey of Methods, Techniques and Hybrid Architectures- - Fouzi Harrag; Abdulmalik Alsalman; Alaa Alqahtani (Journal of Digital Information Management, 2019)
In the last recent years, the customer reviews has attracted an increasing interest by researchers and companies thanks to the advancement in E commerce and business applications. The ability to successfully decide whether a review will be helpful to other customers and thus give the product more exposure is vital to companies that support these reviews, companies like Google, Amazon and Yelp! The problem is that some customers are giving rating in conflict with their comments obliging other reviewers to read the comments to understand the reason of this contradiction. Sentiment analysis is the process of automatically identifying opinions expressed in text on certain subjects. The accuracy of sentiment analysis has a direct effect on decision making in both business and government. Also, recommender system is one of the hot topics in the field of big data, especially with the development and growth of the World Wide Web.

Parking System Development Using Extreme Programming Method- - Johannes Fernandes Andry; Gary Juliawan; Yosua Christian; Jeffry Leonardo; Nicolas (Journal of Digital Information Management, 2018)
In developing cities such as in Jakarta, there are a lot of vehicle parking locations that still use conventional methods, which can harm drivers and also parking area owners alike, the process is slow and unsafe, making many people around feel afraid to use parking locations that are still conventional, the conventional parking lots in Jakarta is too many, sometimes also make people have no other choice but to use unsecured parking lots, theft is the main factor that is difficult to avoid, especially in developing countries like Indonesia, which are not safe, and the location of the parking lot that is very open, makes a lot of opportunities which of course can be used by thieves or irresponsible people. Not only thieves, drivers who do not want to pay for parking, are also a problem for owners of parking lots. With the problems of these users, we plan to make modular parking applications that can be installed easily and cheaply, but because our group is not so large, there are several challenges that we face, such as time and requirements that can increase later, with thus we plan to make this parking application using the Extreme Programming method, which is possible and very suitable for the problems that our group is facing. The use of Extreme Programming turned out to be very helpful, and can also produce an application that matches the existing user stories.

Parking System Development Using Extreme Programming Method - Johannes Fernandes Andry; Gary Juliawan; Yosua Christian; Jeffry Leonardo; Nicolas (Journal of Digital Information Management, 2018)

Performance Measure and Analysis of MPLS and conventional IP network through VoIP: Effect in Video and Audio transmission - Jawad Oubaha; Abderrahmane Ez-zahout (Journal of Networking Technology, 2018)

Play-driven Design: Model for Engaging Person as in Content Sites - Angelo Públio; Sergio Nesteriuk (Journal of Information Organization, 2018)

Private Cloud for College: Architecture and Possibility - Saif Alnuaimi (Journal of Information Technology Review, 2018)

Plagiarism detection in Arabic documents: Approaches, architecture and systems - Kahloula, B.; Berri, J. (Journal of Digital Information Management, 2016)

Paper hijacking: Hijackers are attacking journals for hijacking unpublished papers - Dadkhah, M. (Journal of Digital Information Management, 2015)

Power station flue gas desulfurization system based on automatic online monitoring platform - Liu, X.; Ma, C.; Yang, X.; Yang, C.; Diao, Y. (Journal of Digital Information Management, 2015)

Providing mobile traffic analysis as-a-Service: Design of a service-based infrastructure to offer high-accuracy traffic classifiers based on hardware accelerators - Barbareschi, M.; De Benedictis, A.; Mazzeo, A.; Vespoli, A. (Journal of Digital Information Management, 2015)

The performance evaluation of university scientific research project management based on the FAHP - Wang, B.; Liu, D. (Journal of Digital Information Management, 2014)
Along with the advance of scientific powers strategic of our country, all types and levels funding limit and quantity of college scientific research project have also increased constantly. It is very important to have complete, accurate and fair evaluations for university scientific research project management performance. Fuzzy analytic hierarchy process (FAHP) as a qualitative, a quantitative and comprehensive evaluation method can be able to evaluate the university scientific research project management performance effectively.
Keywords: College research; Fuzzy analytic hierarchy process (FAHP); Fuzzy judgment matrix; Management performance evaluation

Parameters selection in the discrete particle swarm optimization algorithm solving gate and runway combinational optimization problem - Ding, J.; Zhang, Y. (Journal of Digital Information Management, 2013)
Gate and runway combinational optimization (GRCO) problem is of great significance in airport operation. In this paper, experimental analysis is performed on the parameters characteristics of the discrete particle swarm optimization (DPSO) algorithm for combinatorial optimization problems. Inertia weight, acceleration constants and population size all have an important impact on the performance of the algorithm. Optimal values exist in the specific application of the respective parameters. The optimal value interval of the population size does not vary with different acceleration constants when inertia weight is constant. Increasing the population size can improve the solution quality, but the time overhead increases significantly. Finally, each parameters selection guidelines are provided.
Keywords: Airport operation; Discrete particle swarm optimization; Gate and runway combinational optimization; Parameters selection

Production line production planning model of iron and steel enterprise - Jiang, G.; He, E.; Li, G.; Kong, J.; Xie, L. (Journal of Digital Information Management, 2013)
At present, iron and steel enterprise develops towards the direction with many procedure, many process, many variety and many specification, and reaches hundreds and thousands of product series and product mix, how to plan, organize and control steel production, production schedule of its product line are key issues. According to the main characteristics of production line of iron and steel enterprise, how to make aggregate production planning of iron and steel enterprise are analyzed. An aggregate production plan model of product line of iron and steel enterprise is proposed, which is calculated by using standard library function of the Matlab7.0 genetic algorithm toolbox to program. Penalty function was adopted in the course of getting solution. These parameters of scale of father population, crossover probability, mutation probability and penalty factor were combined and optimized. The result obtained is in accordance with the actual conditions of this enterprise basically that the optimization solution to production plans of real iron and steel enterprise by using the algorithm.
Keywords: Aggregate production plan model; Genetic Algorithm; Index terms -iron and steel enterprise; MATLAB; Production line

A Personalization layer for mediation systems - Zaoui, I.; Wadjinny, F.; Chiadmi, D.; Benhlima, L. (Journal of Digital Information Management, 2012)
Mediation systems allow integration of disparate and heterogeneous data sources. Unfortunately, with the increasing number of integrated sources, especially in the context of web, mediator's responses time increases considerably while the answers are not adapted to users profiles. In this paper, we present a personalization layer that makes the mediation system more sensitive to user's preferences. The layer sits between the user and the mediation system. It captures the user profile and performs a smart source selection according to user's interests and quality preferences. Selection is based on similarity measurement between users and sources models. Our solution for personalizing data source selection provides the mediator with a set of relevant data sources. These are then involved in the rewriting process to give more satisfying response.
Keywords: Mediation systems; Personalization; Source selection; User profile

Playing games with information: Investigating perceptions of a mobile content sharing game - Goh, D.H.-L.; Lee, C.S.; Chua, A.Y.K. (Journal of Digital Information Management, 2012)
We introduce Indagator (Latin for explorer), an application which incorporates multiplayer, pervasive gaming elements into mobile content sharing. Indagator allows users to annotate real world locations with multimedia content, and concurrently, provides opportunities for play through engaging interactive game elements. A study of Indagator was conducted to obtain usability feedback, and to examine the impact of the usability of its content sharing and gaming features on participants' intention to use it. Participants used the software to complete a set of tasks and subsequently completed a questionnaire and attended an interview, both of which were to elicit their opinions on the usability of the system. Participants felt that the features in Indagator were able to support the objectives of content sharing and gaming, and that idea of gaming could be a motivator for content sharing. In terms of intention to use, usability of Indagator's gaming features emerged as significant predictors.
Keywords: Mobile Content Sharing Game; Social Computing; Usability; User Evaluation

Password based anonymous authentication with private information retrieval - Nakamura, T.; Inenaga, S.; Ikeda, D.; Baba, K.; Yasuura, H. (Journal of Digital Information Management, 2011)
This paper focuses on authentication with three types of entities: a user who sends an authentication request, a service provider who receives and verifies the request, and a database who supplies the service provider with information for verifying the request. This paper presents novel authentication protocols that satisfy the following important properties: (1) secure against replay attacks and (2) the database cannot identify which user is authenticating. First, we show a protocol which satisfies Properties (2). Second, we show a protocol which satisfies Properties (1) and (2). A key idea of our authentication protocols is to use private information retrieval (PIR) [Chor et al. J. ACM, 1998].
Keywords: Anonymity; Authentication; Privacy protection; Private information retrieval

The performance analysis of a service deployment system based on the centralized storage - Dong, Z.X. (Journal of Digital Information Management, 2011)
Because of its data centralized management characteristic, which conveniently realize resources sharing and the data fast clone, the service deployment technology based on the centralized storage can achieve fast deployment for the system service through the network boot methed or the method of downloading disk image from the remote storage server. However, for the data centralism the I/O load is also congested on the storage server, which creates the drop of the overall system performance and the reducing of the service quality. So we need to test and analyze its performance factors, which provide the clue for the solution of the performance bottleneck. In this paper, we use the SonD deployment system, which is based on the centralized storage, as the analysis prototype to carry on the analysis to the client boot process, evaluate its performance influence factors such as the memory size of storage server, data distribution on the storage server through the real or simulated method, and give suggestion of the performance optimized.
Keywords: Centralized Storage; Performance Analysis; Service Deployment

A practical and secure buyer-seller watermarking protocol - Hu, D.; Li, Q. (Journal of Digital Information Management, 2011)
Digital watermarking is an emerging technology for combating copyright piracy. In real applications, the transaction between a buyer and a seller is done through a specific watermarking protocol, which enables the seller to successfully identify a traitor from a pirated copy, while preventing the dishonest seller from framing an inno cent buyer. In this paper, we propose a new buyer-seller watermarking protocol. Compared to the previous works, it makes two improvements, which make it more practi cal. First, no third party is introduced and hence, the problem of the seller (or buyer) colludes with a third party to cheat the buyer (or seller) is solved. Second,a double watermark insertion is avoided, and then the final quality of the watermarked content is higher and the result of the watermark detection is more accurate.
Keywords: Copy deterrence; Digital copyright protection; Digital watermarking; Watermarking protocol

A practical U-healthcare network with security and QoS - Huang, S.-Y.; Hung, C.-C.; Lee, C.-C. (Journal of Digital Information Management, 2011)
As a consequence of rapid technological development, the normally isolated medical sensor platform is gradually being integrated into networks. However, most ubiquitous or mobile health systems are lacking a system that combines both network security and QoS (Quality of Service). This paper investigates the possible security and QoS methods of a ubiquitous healthcare network platform in OSI (Open System Interconnections)-layers. This network platform is based on the Wireless Overlay Networks (WON) Bluetooth, 802.11 and 802.16 over IPv6 network, and provides a secure and stable U-healthcare platform by including the application of healthcare sensors with RFID, U-healthcare PDA, VoIPv6, falling detection, and patient orientation.
Keywords: Healthcare; IPv6 network; QoS; Security; Ubiquitous

Performance evaluation of fixed and mobile relay in WiMAX system - Mumtaz, S.; Tu, L.T.; Sadeghi, R.; Gameiro, A. (Journal of Digital Information Management, 2010)
Future wireless communication systems are expected to provide more stable and higher data rate transmissions in the whole network. WiMAX is one of the technologies to cover diverse geographic regions. WiMAX covers the high dense urban areas and provide access over large geographic regions in remote rural area. However, in both scenarios it is challenging to cover the entire service area. In both cases relays are foreseen to extend the range of the BS and to increase the system throughput allowing for a cost-efficient deployment and service. As multi-hop/relay has complex interactions between the routing and medium access control decisions, the extent to which analytical expressions can be used to explore its benefits are limited. Consequently simulations tend to be the preferred way of assessing the performance of relays. In this paper, we explain, how to deploy fixed-relay and mobile relay by using computer simulation in WiMAX system and we consistently observed that the throughput is increased and the outage is decreased in the relay-augmented WiMAX network, which is converted to range extension without any capacity penalty, for the realistic range of values of the propagation and other system parameters investigated.
Keywords: Coverage area; Fixed relay; Throughput; WiMAX

Personalized document ranking: Exploiting evidence from multiple user interests for profiling and retrieval - Tamine-Lechani, L.; Boughanem, M.; Zemirli, N. (Journal of Digital Information Management, 2008)
The goal of personalization in information retrieval is to tailor the search engine results to the specific goals, preferences and general interests of the users. We propose a novel model for both user profiling and document ranking that consider the user interests as sources of evidence in order to tune the accuracy of the documents returned in response to the user query. User profiling is performed by managing the user search history using statistical based operators in order to highlight the user short-term interests seen as surrogates for building the long-term ones. The document ranking model's foundation comes from influence diagrams which are extension of Bayesian graphs, dedicated to decision-making problems. Hence, query evaluation is carried out as an inference process that aims at computing an aggregated utility of a document by considering its relevance to the query but also the corresponding utility with regard to the user's topics of interest. Experimental results using enhanced TREC collections indicate that our personalized retrieval model is effective.
Keywords: Data Quality; Grammar Formalism; Integrity Constraint Checking; Spatial Consistency; Topological Relationships; Visual Language Parsing

Palette-based image segmentation using HSL space - Krikor, L.Z.; Baba, S.E.I.; Krikor, M.Z. (Journal of Digital Information Management, 2007)
This paper describes a palette-based colored image segmentation system. In this paper we analyzed the properties of Hue, Saturation, and Luminance (HSL) color space with emphasis on the visual perception of the variation in Hue, Saturation and Luminance values of palette colors. The proposed algorithm based on the concept of re-coloring the palette colors of 256-color images using the properties of HSL color space and segmenting true type images by taking part of the image, generating a palette to it then apply the method to segment the selected region. After re-coloring of the palette colors the colors in the image will be re-colored according to its new palette, and as a result the image will be segmented to different segments.
Keywords: HSL space; Image segmentation

Performance of integrated wired (Token ring) network and wireless (PRMA) network - Al-Amawi, A.; Khanfar, K. (Journal of Digital Information Management, 2007)
Computer networks can be built using either wired or wireless technology. Although wired network has been the traditional choice, wireless technologies are becoming more popular. One of the most challenges is to have an existing wired network to which a wireless network extension could be added. Specifically the challenge is to connect a group of wireless networks through a wired backbone. The primary purpose of this study is to develop an integrated mathematical model by integrating Packet Reservation Multiple Access (PRMA) one of the most wireless LAN protocols and Token Ring wired network protocol. Performance parameters of an integrated PRMA-Token Ring model such as delay and throughput have be analyzed. The numerical analysis presented in this paper may help in studying the affect of some parameters on the system performance and stability.
Keywords: Hybrid network; Network; Performance; PRMA; Token ring; Wireless; Words

Personalized searching by learning wordnet-based user profiles - Semeraro, G. (Journal of Digital Information Management, 2007)
The amount of information available on the Web and in Digital Libraries is increasing over time. In this context, the role of user modeling and personalized information access is becoming crucial: Users need a personalized support in sifting through large amounts of retrieved information according to their interests. Information filtering and retrieval systems relying on this idea adapt their behavior to individual users by learning their preferences during the interaction in order to construct a profile of the user that can be later exploited in the search process. We propose a novel technique to learn user profiles which exploits word sense disambiguation based on the WordNet lexical database, in an attempt to produce semantic user profiles that might discover topics semantically closer to the user interests. Semantic profiles are used in the definition of a retrieval model that turns the traditional document-query search paradigm into a novel document-query-profile paradigm. As an example of this paradigm, we present an extension of the vector space model in which profiles are used to modify the ranking of search results obtained in response to a query, hopefully putting personally relevant items on the top of the result list. Experimental results in a movie retrieval scenario indicate that the proposed model to personalize Web search is effective.
Keywords: Machine learning; Personalization and information filtering; User modeling; WordNet

Pre-processing and Path Normalization of a web graph used as a social network - Teja, C.B.; Mitra, S.; Bagchi, A.; Bandyopadhyay, A.K. (Journal of Digital Information Management, 2007)
Many efforts have been made for compression of web graphs. Most of these methods are suitable for search engines and are centered around encoding links and URLs efficiently. The purpose is to handle a large set of web pages in the main memory against any web based search. The authors of the present paper are interested in studying web graph as a social network and to develop a data model for it. So, suitable compression techniques, which are space efficient for disk based storage, are required. This paper has provided a two level compression technique. In the first level, the structural properties of a graph are studied and strongly connected components are fused to reduce the original graph to a DAG. Paths on this DAG are then stored efficiently using a Path Normalization technique. Space complexity expressions indicate the efficiency of the method. Relevant operators required for accessing the original graph through the compressed representations have also been discussed. Important earlier works have been referred to indicate the requirements of the present approach.
Keywords: Compression technique; Path normailisation technique; Social software; Web search

Promotion of local to global operation in train control system - Khan, S.A.; Zafar, N.A. (Journal of Digital Information Management, 2007)
Railway interlocking system is a safety critical system. Its failure can cause the loss of human life, severe injuries and loss of money. Therefore the complication of this type of system requires advanced methodologies, which provide complete security and quality of a system. One way of achieving this goal is by using formal methods, which are mathematically based languages, techniques and tools used for specifying and verifying such systems. This paper provides the control of trains in a sector of moving block interlocking system using the approach of promotion. The promotion is the approach used to link the local state with a global state in Z specifications. The control comprises three components, i.e. sector, trains and security of a train in a sector.
Keywords: Formal specification; Predicate logic; Schema calculus; Z notation

Parallel algorithms for the generalized same generation query in deductive databases - Arman, N. (Journal of Digital Information Management, 2006)
The intelligence of traditional database systems can be improved by recursion. Using recursion, relational database systems are extended into knowledge-base systems (deductive database systems). Linear recursion is the most frequently found type of recursion in deductive databases. Deductive databases queries are computationally intensive and lend themselves naturally to parallelization to speed up the solution of such queries. In this paper, parallel algorithms to solve the generalized fully and partially instantiated forms of the same generation query in deductive databases are presented. The algorithms use special data structures, namely, a special matrix that stores paths from source nodes of the graph representing a two-attribute normalized database relation to all nodes reachable from these source nodes, and a reverse matrix that stores paths from any node to all source nodes related to that node.
Keywords: Deductive databases; Linear recursive rules; Parallel databases; Same generation query

Peer-to-peer content search supported by a distributed index in a publication/search model - Tolosa, G.H.; Peri, J.A.; Bordignon, F.R.A. (Journal of Digital Information Management, 2006)
Peer to-peer networks (P2P) are considered a valid approach for the construction of distributed systems. Further research projects in the last few years have focused on using this kind of networks as an alternative for solving different situations that have traditionally required centralized servers, such as search engines. This paper deals with the problem of content search in highly distributed and dynamic environments. We propose and evaluate a distributed index model built upon a peer-to-peer network which supports complete indexing of text documents and allows searching by content. A distinctive feature of this proposal is that it requires no specific network topology or hierarchy. Evaluations with different settings were performed by simulating a 10,000-node network, where each node had the capability to share documents. With regard to the traffic generated, experiments show an improvement in efficiency of between 84% and 93% over similar systems like Gnutella. The evaluation of retrieval performance using a test collection showed that the P2P system was able to achieve the same level of performance as the centralized system. It was also found that the amount of traffic generated by this model varies between 80 and 225 Kb per set of query and answers.
Keywords: Distributed index model; Nodes; P2P network evaluation; P2P networks

Providing support for interaction with consistent multimedia presentations - Elias, S.; Easwarakumar, K.S.; Mathew, L.; Chbeir, R. (Journal of Digital Information Management, 2006)
Multimedia presentations are generally specified in terms of spatial and temporal relations between the media objects involved. Creation of these presentations, and interactions with them during their play-out, require an effective mechanism for handling the specifications dynamically. These specifications could result in inconsistencies, which need to be checked and resolved. Moreover, consistent presentations could become inconsistent due to interactions during the playout. Our main contribution is the design of an algorithm which aids in resolving these consistency issues dynamically and efficiently. The other salient features of our approach are a new composite spatio-temporal operator and an effective relaxation policy. We have developed a prototype which helps to study the effectiveness of the proposed approach. Thus, this paper presents an interactive multimedia presentation mechanism, which maintains a consistent and complete set of constraints during authoring and play-out of the presentation.
Keywords: Completeness checking; Consistency checking; Distributed multimedia presentations; Spatio-temporal relations

Pruning techniques in associative classification: Survey and comparison - Thabtah, F. (Journal of Digital Information Management, 2006)
Association rule discovery and classification are common data mining tasks. Integrating association rule and classification also known as associative classification is a promising approach that derives classifiers highly competitive with regards to accuracy to that of traditional classification approaches such as rule induction and decision trees. However, the size of the classifiers generated by associative classification is often large and therefore pruning becomes an essential task. In this paper, we survey different rule pruning methods used by current associative classification techniques. Further, we compare the effect of three pruning methods (database coverage, pessimistic error estimation, lazy pruning) on the accuracy rate and the number of rules derived from different classification data sets. Results obtained from experimenting on different data sets from UCI data collection indicate that lazy pruning algorithms may produce slightly higher predictive classifiers than those which utilise database coverage and pessimistic error pruning methods. However, the potential use of such classifiers is limited because they are difficult to understand and maintain by the end-user.
Keywords: Association rule; Associative classification; Classification; Data mining; Rule pruning